2018
DOI: 10.1038/s41467-018-06069-5
|View full text |Cite
|
Sign up to set email alerts
|

Notch2 controls non-autonomous Wnt-signalling in chronic lymphocytic leukaemia

Abstract: The Wnt signalling pathway, one of the core de-regulated pathways in chronic lymphocytic leukaemia (CLL), is activated in only a subset of patients through somatic mutations. Here we describe alternative, microenvironment-dependent mechanisms of Wnt activation in malignant B cells. We show that tumour cells specifically induce Notch2 activity in mesenchymal stromal cells (MSCs) required for the transcription of the complement factor C1q. MSC-derived C1q in turn inhibits Gsk3-β mediated degradation of β-catenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…In brief, it was shown that the central regulator of WNT signalling, β -catenin, was stabilised by direct cell contact to BMSCs. The underlying mechanisms involve phosphorylation of GSK3-β and transcriptional up-regulation of N-Cadherin, thereby allowing β-catenin to accumulate and to co-activate transcription in the nucleus [18]. Notably similar results were obtained by other groups in acute lymphoblastic leukaemia, demonstrating that microenvironment-mediated stabilisation of β-catenin also increases drug resistance [20,21].…”
Section: Bmscs and Oncogenessupporting
confidence: 55%
See 3 more Smart Citations
“…In brief, it was shown that the central regulator of WNT signalling, β -catenin, was stabilised by direct cell contact to BMSCs. The underlying mechanisms involve phosphorylation of GSK3-β and transcriptional up-regulation of N-Cadherin, thereby allowing β-catenin to accumulate and to co-activate transcription in the nucleus [18]. Notably similar results were obtained by other groups in acute lymphoblastic leukaemia, demonstrating that microenvironment-mediated stabilisation of β-catenin also increases drug resistance [20,21].…”
Section: Bmscs and Oncogenessupporting
confidence: 55%
“…Recent data from our group have shown that, in a contact dependent manner, leukemic cells specifically activate NOTCH2 signalling in BMSCs with an associated loss of NOTCH1. This activation leads to the production of soluble factors, such as C1q, which has been shown to promote CLL cell survival, similar to effects observed on metastatic lesions of solid tumours [18,71]…”
Section: Activated Signalling Pathways In Remodelled Bmscsmentioning
confidence: 68%
See 2 more Smart Citations
“…In malignant pleural mesothelioma, C1q binds to hyaluronic acid in the tumor microenvironment and enhances tumor proliferation (73). C1q secreted by mesenchymal stromal cells mediates the activation of β-catenin in chronic lymphocytic leukemia and enhances malignant progression (74). On the other hand, properdin, a positive regulator of complement activity, induces endoplasmic reticulum-stress response and exerts a tumor suppressive role in breast cancer (75).…”
Section: Complement In the Tumor Microenvironmentmentioning
confidence: 99%